Pelatihan Pembuatan e-LKPD Inovatif menggunakan liveworksheet pada Mata Pelajaran Matematika SD - Leni Yunita Rahmawati; Cahya Hidayati; Nabilah Putri Febriyani; Putri Zudhah Ferryka (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
Technological developments in this era have an impact on several aspects of life. One of them is in the field of education. Currently, teachers and prospective teachers are required to have creative and innovative teaching skills. Technological developments have also produced many new innovations to support the learning process that teachers can apply in the learning process. New innovations that can support the learning process include the use of media and platforms that can be used to create student worksheets. This service activity is training in the use and creation of student worksheets using the Liveworksheet platform for Elementary School Teacher Education study program students. The aim of this activity is to introduce the liveworksheet platform and also provide training for PGSD students in creating innovative e-LKPD using liveroksheet. The method in this research is training carried out face-to-face or offline, which consists of two sessions, namely the delivery of material and the practice of making e-LKPD. The results of this service showed positive results where all students who participated in the training gained knowledge and skills in using and creating e-LKPD via the live worksheet platform